Computation of Heterojunction Parameters at Low Temperatures in Heterojunctions Comprised of n-Type β-FeSi2 Thin Films and p-Type Si(111) Substrates Grown by Radio Frequency Magnetron Sputtering - Phongsaphak Sittimart; Adison Nopparuchikun; Nathaporn Promros (Advances in Materials Science and Engineering)
In this study, n-type β-FeSi2/p-type Si heterojunctions, inside which n-type β-FeSi2 films were epitaxially grown on p-type Si(111) substrates, were created using radio frequency magnetron sputtering at a substrate temperature of 560°C and Ar pressure of 2.66×10-1 Pa. The heterojunctions were measured for forward and reverse dark current density-voltage curves as a function of temperature ranging from 300 down to 20 K for computation of heterojunction parameters using the thermionic emission (TE) theory and Cheung’s and Norde’s methods. Computation using the TE theory showed that the values of ideality factor (n) were 1.71 at 300 K and 16.83 at 20 K, while the barrier height (ϕb) values were 0.59 eV at 300 K and 0.06 eV at 20 K. Both of the n and ϕb values computed using the TE theory were in agreement with those computed using Cheung’s and Norde’s methods. The values of series resistance (Rs) computed at 300 K and 20 K by Norde’s method were 10.93 Ω and 0.15 MΩ, respectively, which agreed with the Rs values found through computation by Cheung’s method. The dramatic increment of Rs value at low temperatures was likely attributable to the increment of n value at low temperatures.